Thermal and dispersion stability of carbon nanotubes (SW-CNT)-carboxymethyl-cellulose(CMS) in aqueous - Jameel, Ahmad Tariq (s.n, 2012)
Nano-fluid is a new engineering material consisting of nano-meter sized particles dispersed in a base fluid. Single-walled carbon nanotubes (SWNT) are structurally unique material that exhibit excellent mechanical, electrical, thermal and optical properties. SWNT offer potential promise for a number of novel applications.In this study, SWNT has been used to produce nano-fluid with distilled water as base fluid and carboxymethyl sellulose (CMC) as surfactant for dispersing SWNT ropes into individual well separated tubes in aqueous solution.